Noise and Vibration Reduction in Permanent Magnet Synchronous Motors –A Review - Lakshmikanth S; Natraj. K.R; Rekha. K.R (Institute of Advanced Engineering and Science, 2012)
A detailed study of the mechanics of vibration and acoustic noise in permanent magnet synchronous motors due to electromagnetic origins. This paper reviews the various noise and vibrations reduction strategies from classical to state of art techniques. The recent research in development of wavelet controller, starting from brief review and the analytical analysis of acoustic noise and vibrations in Permanent magnet synchronous motor is presented. Application of wavelet transforms in the area of denoising and filtering is also explored.DOI:http://dx.doi.org/10.11591/ijece.v2i3.322